Kultur Jaringan Tanaman dalam Produksi Senyawa Antikanker: Artikel Ulasan - Maisyarah, Intan Timur; Silvia, Nurfianti (Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, 2021)
Plant tissue culture is one of the main methods to supply the demand of anticancer drug derived from plants. Global demand for anticancer drugs from plants is very high, due to cancer is one of the main diseases that has the highest mortality rate in the world. This review article was written with the aim to summarize the latest developments plant tissue culture techniques to produce secondary metabolites with anticancer activity in the last 10 years. The method used to write this article is a literature review on the PubMed and Google Scholar database. The result showed that plant tissue culture techniques can increase the production of anticancer compounds derived from plants, especially through optimization of growth media, elicitation, and precursor feeding.